#Instagrameable. Prácticas y rutinas de un grupo de fans de las social media influencers Katy Esquivel y Tana Rendón y la construcción de su capital cultural y narrativas femeninas - Félix Seras, Diana (2022)
This research aims to understand the practices and routines of a group of Peruvian fans of social media influencers Katy Esquivel and Tana Rendón on Instagram and how this group builds cultural capital and female narratives from media content. To answer this question, digital ethnography was used as the main fieldwork methodology to find fans and analyze their posts and social interactions on the social network Instagram. Likewise, this research conducted remote and only face-to-face interviews before social isolation due to COVID-19. Among the findings, the practices and routines created around the media content of celebrities stand out, in addition to the advice and lessons learned by fans to become entrepreneurs of themselves and serve as cultural references that give meaning to their lives. The narratives of social media influencers become a second school for their fans, allowing them to build cultural capital, reconstruct their subjectivities and consolidate their own identity as part of a global and cosmopolitan middle class.